The Scottish Children's Research Network: challenges, opportunities and achievements. (May 2013) - Helms, Peter J; Dicks, Pamela
Although research in children can be challenging for investigators, children and their families, it is only through well-designed and ethical studies that improvements in diagnosis, disease prevention and disease management can be made. The Scottish Children's Research Network (ScotCRN), which was established in 2006 with core funding from the Scottish Chief Scientist Office, combines the benefits of central coordination of adopted research, including clinical trials, with the advantages of practical infrastructure support at local investigator level. Close collaboration is maintained with the equivalent networks in the other three UK health administrations and with emerging equivalent networks across Europe. Access to clinical investigators and patient populations across the whole range of pediatric specialties and the young person's advisory group provide valuable resources for potential academic and industry partners. Encouraging pediatric clinicians to participate in research and providing practical support has resulted in a significant broadening of the pediatric- and child-health research base and level of activity in Scotland. Future challenges will include maintaining this momentum and advocacy for the specific needs of children and families engaged in research.